Preemptive Ibuprofen and Orally Administered Dexamethasone for Prevention of Pain and Swelling following Implant Surgery - Amin, Fatemeh; Soleimani Shayesteh, Yadollah; Alikhasi, Marzieh (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Introduction: The post-operative pain and swelling are frequently observed after different surgical procedures. Orofacial pain management is a challenging topic for the dental-medical profession. The main objective of this study was to compare the effects of two designed medical regimens in the context of post-operative management of pain and swelling following simple dental implant surgery. Materials and Methods: In this randomized and double-blinded controlled clinical trial, a total of 39 implants were placed in 31 patients by one clinician. Patients were divided into the test and control groups. Before surgery, each patient in the control group received 1gr of amoxicillin and 400 mgr of ibuprofen, and each one in test group received 1gr of amoxicillin, 400 mgr of ibuprofen and 0.5 mgr of dexamethasone. Antibiotic regimen, together with analgesics and anti-inflammatory treatment was provided after surgery for both groups. Pain was measured using visual analogue scale in days 1, 3 and 6 after surgery. Swelling was evaluated by a verbal scale in day 6. Also, the impact of following factors gender, age, duration of surgery, type and number of implant on pain and swelling was measured by the general linear model analysis. Results: The majority of patients in both study groups reported the pain to be mild, with peak intensity occurring at 24 hours after operation. No significant difference was observed across the groups for any given time. Also, there was no significant difference between two groups regarding their swelling profile. Conclusion: The experiments provide evidence that both of these methods are effective in pain and swelling reduction.